Rings of Power or in Search of Early Elites - Manzura, Igor (Archaeologia Lituana, 2022)
The article discusses the problem of identification of prehistoric elites on the example of the Usatovo culture. Archaeological evidence allows us to discern in the culture three separate strata or classes which are conditionally designated as the Nobles, the Honoured, and the Commoners. Social elite represented a core within the noble class. It is distinguished by specific attributes which illustrate its attempts to resolve one of the most complex problems of any elite – to reconcile tension between “universalism” and “particularism”. The first quality is realized in ritual performance through manipulation of material objects whereas the second one is realized by means of sumptuary customs along with other methods. The emergence of the elites in the Usatovo culture became possible due to specific combination of objective factors which were successfully utilized by new social leaders.
Keywords: North Pontic region; Early Bronze Age; the Usatovo culture; cultural anthropology; complex society; social hierarchy; elites